Using Kahoot Application as Interactive Media in the Arabic Speaking Skills Development - Yasin, Agus; Rinawati, Tiara Eki Wahyu; Putri, Nabila Rahayu (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study examines the impact of using the Kahoot! application as an interactive learning medium for teaching Arabic, focusing on developing students' speaking skills and learning motivation. The background highlights the need to enhance student engagement and motivation, which is often limited by traditional teaching methods. The research employs a descriptive qualitative approach based on literature, analyzing studies related to Kahoot! in language learning contexts. Results indicate that Kahoot! is effective in boosting student engagement through its interactive and enjoyable gamification approach. It provides immediate feedback, accelerating students' understanding of their mistakes, and fosters a healthy competitive atmosphere in the classroom, significantly enhancing learning motivation. In conclusion, Kahoot! proves to be an effective interactive tool that improves language skills, particularly speaking, and creates a dynamic, non-monotonous learning environment, showing great potential for integrating Kahoot! into Arabic teaching, especially in the digital era.